Content Validity of Android-Based Sport Training Program Monitor For Tennis Players - Rivan Saghita Pratama; Sri Haryono; Abdul Hafidz; Ali Md Nadzalan; Jaffry Bin Zakaria; Teguh Santosa; Sunanto Sunanto; Agus Himawan; Nur Ahmad Muharram; Septyaningrum Putri Purwoto (Sport i Turystyka)
Tracking an athlete’s training program is crucial for objectively monitoring training activities, physical development, skill acquisition, and program adjustments. This research aims to develop an Android-based application for monitoring sports training programs tailored for tennis players. The study employs both quantitative and qualitative research methods, analyzed using Aiken’s V formula. Participants included 5 licensed tennis trainers, 5 strength and conditioning experts, and 3 technology specialists. The results show V coefficient values ranging from 0.90 to 1.00, with  a mean value of 0.97, indicating high validity according to tennis coaching experts. Evaluation of the physical condition of tennis players yielded V coefficient values between 0.90 and 1.00, with a mean of 0.96, reflecting high validity of all items. Furthermore, expert assessments in technology and informatics produced V coefficient values from 0.83 to 1.00, with a mean of 0.93, indicating high validity of all items. Therefore, this research confirms that all test items have a high level of content validity. With this high validity, the application can be effectively used by coaches to manage the training programs and daily activities of tennis players.